Acute alcohol use among suicide decedents in 14 US states: impacts of off‐premise and on‐premise alcohol outlet density. (13th November 2014) - Giesbrecht, Norman; Huguet, Nathalie; Ogden, Lauren; Kaplan, Mark S.; McFarland, Bentson H.; Caetano, Raul; Conner, Kenneth R.; Nolte, Kurt B.
Abstract Aims To estimate the association between per capita alcohol retail outlet density and blood alcohol concentration (BAC) from 51 547 suicide decedents and to analyse the relationship between alcohol outlet density and socio‐demographic characteristics among alcohol‐positive suicide decedents in the United States by racial/ethnic groups and method of suicide. Design Analysis of US data, 2003–11, National Violent Death Reporting System. Setting Suicide decedents from 14 US states. Participants A total of 51 347 suicide decedents tested for BAC. Measurements BAC and levels were derived from coroner/medical examiner reports. Densities of county level on‐premises and off‐premises alcohol retail outlets were calculated using the 2010 Census. Findings Multi‐level logistic regression models suggested that higher off‐premises alcohol outlet densities were associated with greater proportions of alcohol‐related suicides among men—for suicides with alcohol present [BAC >0; adjusted odds ratio (AOR) = 1.08, 95% confidence interval (CI) = 1.03–1.13]. Interactions between outlet density and decedents' characteristics were also tested. There was an interaction between off‐premises alcohol availability and American Indian/Alaska Native race (AOR = 1.36; 95% CI = 1.10–1.69) such that this subgroup had highest BAC positivity. On‐premises density was also associated with BAC >0 (AOR = 1.07; 95% CI = 1.03–1.11) and BAC ≥0.08 (AOR = 1.05; 95% CI = 1.02–1.09) among male decedents. Conclusions In the United States, the density of both on‐ and off‐premises alcohol outlets in a county is associated positively with alcohol‐related suicide, especially among American Indians/Alaska Natives.